Socialization of The Dangers of Drug Abuse and Its Impact on Mental Health in The Community - Wardany, Nadia Sintia; Pragholapati, Andria; Perdani, Agni Laili; Wahdini, Ridha; Sumartini, Sri; Wahyoe, Asih Purwandari; Suparto, Tirta Adikusuma; Sulastri, Afianti; Rohaedi, Slamet; Rahmi, Upik (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Drug abuse remains a serious problem in Indonesia, with devastating effects both physically and mentally. This community service project explored public knowledge about the dangers of drug abuse and its impact on mental health. The activity was conducted at the Cigugur Tengah Community Health Center in Cimahi. Education and health promotion through interactive counseling, group discussions, and collaboration with the National Narcotics Agency (BNN) and medical personnel. This activity involved 30 participants, including cadres and families/caregivers of patients with mental disorders. Showed an increase in participants' knowledge regarding the identification of types of drugs, their psychological effects, and prevention and early detection strategies. The discussion also highlighted the importance of the role of families and the community in supporting prevention efforts. This outreach program effectively raised public awareness and served as the first step in building a drug-aware environment that supports overall mental health. Keywords: Community, Drug Abuse, Mental Health